Role of Vitamin D Supplementation on Symptom Score and Quality of Life in Patients with Chronic Urticaria - A Hospital Based Randomized Controlled Trial - Nishtha Loona, Tanishq Gupta*, Manish Kumar Maity, Mamta Naagar, (South Eastern European Journal of Public Health, 2025)
Background - Urticaria is defined as “a transient, well-demarcated erythematous swelling of the skin, associated with itching, which usually resolves within 24 hours” One-tenth to one-fifth of the total population is likely to suffer from urticaria in a lifetime, while 1% of the general population experience chronic urticaria (>6 weeks). There are few available treatments, where Vitamin D is a possible substitute and safe alternative as an immunoregulatory molecule. Methods - This is a Randomized Control Trail of 100 patients with 50 patients in each group (Group A and B) using UAS7 and CUQ2oL scores. Group A received oral antihistamine (tab. Levocetirizine ranging from 5 mg to 20 mg/day based on the severity of CU, for 12 weeks) along with vitamin D supplementation (60,000 IU of oral vitamin D3 weekly for 4 weeks and one dose at the end of 8 weeks (total 5 doses) and Group B received only oral antihistamine therapy. Results - After 12 weeks, UAS7 scores in both groups declined considerably and a larger reduction was found in Group A and the total CUQ2OL score was also more significantly improved in Group A in comparison to Group B after the study completion. Conclusion - Add-on therapy with vitamin D3 (60000 IU/week) to subjects with CU can result in a decrease in urticaria symptoms and improve the quality of life of patients over time. So vitamin D3 could be considered a potentially safe and inexpensive immunomodulator to benefit patients with CU.